2006
DOI: 10.7205/milmed.171.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Human Immunodeficiency Virus Type 1 and Risk Practices among Female Commercial Sex Workers in Isla Margarita, Venezuela

Abstract: Sexual transmission represents the principal mode of transmission for human immunodeficiency virus type 1 (HIV-1) worldwide. We examined the HIV-1 seroprevalence and risk factors for infection among 613 female commercial sex workers (FCSW) in Isla Margarita, Venezuela. Recruitment was conducted in street venues and working locations. None of the FCSW tested positive for HIV; this correlated with the low self-reported rates of sexually transmitted infections (6%), drug use (<20%), and alcohol abuse (12%). Condo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…For studies reporting on alcohol use frequency, 12.0–100% used alcohol in the past month [ 41 43 , 50 52 , 57 , 60 , 63 , 80 92 ]; 89.0–93.7% reported using alcohol in the last 12 months [ 93 , 94 ]; 6.4–77.8.0% used alcohol at least once a week [ 29 , 41 , 42 , 52 , 60 , 63 , 85 , 87 90 , 95 102 ] and 10.0–64.6% used alcohol at least once a month [ 29 , 52 , 60 , 63 , 85 , 87 , 89 , 90 , 97 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For studies reporting on alcohol use frequency, 12.0–100% used alcohol in the past month [ 41 43 , 50 52 , 57 , 60 , 63 , 80 92 ]; 89.0–93.7% reported using alcohol in the last 12 months [ 93 , 94 ]; 6.4–77.8.0% used alcohol at least once a week [ 29 , 41 , 42 , 52 , 60 , 63 , 85 , 87 90 , 95 102 ] and 10.0–64.6% used alcohol at least once a month [ 29 , 52 , 60 , 63 , 85 , 87 , 89 , 90 , 97 ].…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies reported data on daily alcohol use with a reported prevalence that ranged from 8–59% [ 29 , 49 , 71 , 85 , 87 , 88 , 90 , 95 , 96 , 102 , 130 , 131 ]. The pooled prevalence of daily alcohol use among FSWs from LMICs is 26% (95% CI: 17–36%) ( I 2 = 99.26) ( Fig 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…A study in Scotland reported that 92% of FSWs used alcohol in the last week (Plant et al, 1990). In terms of the drinking 'frequency', 12-78% of FSWs (median 33%) consumed alcohol daily (Peltzer et al, 2004;Philpot et al, 1989;Gossop et al, 1994;Estebanez et al, 1997;Inciardi and Surratt, 2001;Inciardi et al, 2005;Surratt and Inciardi, 2004;Wechsberg et al, 2005;Yadav et al, 2005;Munoz et al, 2006;Pell et al, 2006); 24-92% of FSWs (median 47.9%) reported weekly use (Plant et al, 1990;Folch et al, 2008;Witte et al, 1999;Peltzer et al, 2004;Wechsberg et al, 2005); and 45.9-75% of FSWs (median 72.1%) reported monthly use (Hagan and Dulmaa, 2007;Inciardi and Surratt, 2001;Surratt, 2007;Kayembe et al, 2008).…”
Section: Patterns Of Alcohol Usementioning
confidence: 99%
“…The lower self-reported HIV prevalence in our sample may point to the success of the Venezuelan National HIV/AIDS Program, operational for the past five years, in providing ART free of charge. 7,18,19 Though scarce information exists on engagement in HIV medical care among MSM, the available literature indicates that among the general population currently living with HIV more than 50% are prescribed treatment. 18,20 Similarly, over three-fourths of MSM in our sample who reported living with HIV were engaged in HIV-related medical care, further suggesting the strength of existing comprehensive HIV services.…”
Section: Discussionmentioning
confidence: 99%
“…Key populations in Venezuela are believed to be MSM and female sex workers (FSWs). 3,68 Compared to other countries in Latin America where evidence suggests heightened vulnerability to HIV among transgender women and sex workers in addition to MSM, there is a dearth of research to support these claims in Venezuela. 9 The scarcity of evidence regarding HIV risk factors for key populations may be due in part to the social, political and economic climate in Venezuelan over the past few decades.…”
Section: Introductionmentioning
confidence: 99%